2021
DOI: 10.3390/pathogens10030284
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic Activity of Antioxidants: In Vitro Effects on the Liver Fluke Opisthorchis felineus

Abstract: Currently, molecular parasitologists are searching for new agents against trematodiases. Redox metabolism is important for parasites as far as long-lived adult parasites inside a mammalian host are exposed to redox challenges. Antioxidants have been poorly studied as anthelmintic agents, in particular against the foodborne trematodes. Study of in vitro anthelmintic activity of nonenzymatic natural and synthetic antioxidants of various chemical structures was performed using standard motility and mortality assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It has been emphasized that the balance between oxidation and antioxidants is critical to a healthy biological system. Low doses of antioxidants may be beneficial for this system, but higher amounts may violate the balance (Mordvinov et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been emphasized that the balance between oxidation and antioxidants is critical to a healthy biological system. Low doses of antioxidants may be beneficial for this system, but higher amounts may violate the balance (Mordvinov et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…felineus by using motility and mortality assays, whereby the most effective substance on the motility of adult flukes was quercetin with an IC50 value of 5.1 μM. On the other hand, a concentration of 10 μM flavone led to a mortality of 22-35% by day 15, which was significantly higher than that of untreated worms (Mordvinov et al 2021). Echinococcosis represents a tapeworm cosmopolitan zoonotic disease where dogs are definitive hosts of the parasite (adult worms), while livestock and humans are intermediate hosts (larval, cystic form).…”
Section: Studies That Examined the Antiparasitic Efficacy Of Plant Pr...mentioning
confidence: 99%
“…The significant decrease in the level of biliary intraepithelial neoplasia that we observed, as well as a decrease in gene expression and production of pro-inflammatory proteins, can be explained, among other things, by a decrease in the level of parasitic load in hamsters. In addition, preliminary data showed that SkQ1 affects the motility of juvenile and adult O. felineus worms in vitro [24]. Therefore, we assessed the anthelmintic activity of SkQ1 in vivo.…”
Section: Evaluation Of Anthelmintic Properties Of Skq1 In Vivomentioning
confidence: 99%